Does "Overall Catastrophic Health Care Expenditure" Make Sense? - Kamran BAGHERI LANKARANI; Sulmaz GHAHRAMANI (Tehran University of Medical Sciences, 2018)
Does "Overall Catastrophic Health Care Expenditure" Make Sense?